Mathematical Creativity in Secondary Education: Conceptual and Assessment Evolution (2016-2025) - B. Widya Melati Patricia; Duano Sapta Nusantara; Rohati Rohati; Kgaladi Maphutha (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Mathematical creativity is increasingly recognized as an essential competency in 21st-century mathematics education, as it underpins students’ capacity for higher-order thinking and adaptive problem-solving. However, existing studies have examined it in isolation without integrating publication trends, conceptual evolution, and assessment methods within a unified analytical framework. This study addresses that gap through a systematic literature review of mathematical creativity in secondary education from 2016 to 2025. Following the PRISMA 2020 guidelines, searches were conducted in the Scopus and ScienceDirect databases. From 544 initial records, 23 articles met eligibility criteria and were analyzed through bibliometric analysis, thematic synthesis, and methodological categorization. Results revealed a substantial increase in publications, with 68.9% of studies published during 2023–2025, driven by curriculum reforms, technology integration, and post-pandemic pedagogical transformation. Conceptualization evolved from Torrance’s traditional four-component framework toward more integrative models emphasizing collaborative processes and contextual problem-solving. Assessment methods showed balanced distribution: quantitative tests (39.1%), qualitative approaches (34.8%), and mixed methods (26.1%). Practically, the findings offer actionable guidance for curriculum developers, teachers, and policy makers to foster mathematical creativity more effectively, while theoretically, the holistic integration of three analytical dimensions provides a replicable model for future systematic reviews in mathematics education.